Antimalarial secondary metabolites from Morinda lucida - Chithambo, Bertha (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
Antimalarial activities of secondary metabolites from Morinda lucida (Rubiaceae), were investigated. Even though M. lucida is traditionally used to treat malaria, diabetes, jaundice, hypertension, dysentery and many other diseases, the compounds in this plant have not yet been fully investigated and characterised. Most of the studies that have been done on this plant focused on the medicinal properties of the crude extracts but have not gone further to isolate and characterise the compounds. In this study, the methanol - dichloromethane crude extract from the bark of M. lucida was fractionated into fractions 1-8. Fractions 2-5 were purified in order to isolate active secondary metabolites. The isolated pure compounds were characterised and identified. An in vitro antimalarial assay was carried out on the crude extract, fractions, pure compounds and solutions made from different combinations of pure compounds using the parasite lactate dehydrogenase (pLDH) assay. An IC50 done on the methanolic crude extract gave a value of 25 µg/mL. The % cell viability for the crude extract in cell toxicity assay remained at 100%. Each of the pure compounds tested had very little activity. Their activities were increased when samples from the different compounds were mixed. One of these mixtures reduced malaria viability to about 22 % at 20 µM and gave an IC50 value of 17 µM. Antibacterial assays were also carried out on the crude extract and fractions. Fractions 2 and 3 were relatively active (MIC values ranging between 125-1000 µg/mL) against M. cattarhalis and E. faecalis. Fraction 2 was also the most active on S. typhimurium and S. aureus (MIC value of 1000 µg/mL) compared with the other fractions. This same fraction also showed some activity against M. tuberculosis with MIC90 and MIC99 values of 40.9 and 46.3 µg/mL respectively in an anti-tuberculosis assay.The following compounds, comprising of iridoids (asperuloside and asperulosidic acid), terpenoids (stigmasterol, P-sitosterol, campesterol, lanosterol and cycloartenol) and anthraquinones [5,15-O-dimethylmorindol, 1,7-dihydroxy-2-methoxy-5-(methoxymethyl) anthraquinone and 1,6-dihydroxy-2-methoxy-5-(methoxymethyl)anthraquinone], were isolated. All these compounds have been isolated from different plants before with the exception of 1,7-dihydroxy-2-methoxy-5-(methoxymethyl)anthraquinone and 1,6-dihydroxy-2-methoxy-5-(methoxymethyl)anthraquinone which were tentatively assigned the structures due to insufficient data. To the best of our knowledge, this is the first report on the identification of all of the mentioned compounds, with the exception of ß-sitosterol and stigmasterol, from M. lucida. Molecular docking was performed on one of the isolated anthraquinones (5,15-O- dimethylmorindol) to check if it can bind to cytochrome bci, a known target for atovaquone. This compound interacted with the same amino acids that atovaquone, a well known antimalarial agent, interacted with on cytochrome bc1 indicating a possible similar mode of action.
Keywords: Botanical chemistry; Anthraquinones; Antimalarials; Rubiaceae -- Therapeutic use; Malaria -- Treatment